(untitled) (Nordic Journal of Practical Theology, 2017)
Anne H. Balsnes, Solveig Christensen, Jan Terje Chri-stoffersen, Hallvard O. Mosdøl (red.) Gudstjeneste à la carte Øyvind M. Eide: Fridtjov S. Birkeli Giganten og gåten